Always remain suspicious: a case study on tracking down a technical artefact while measuring IR-RF - Kreutzer, Sebastian; Murari, Madhav Krishna; Frouin, Marine; Fuchs, Markus; Mercier, Norbert (Ancient TL, 2017)
Identifying systematic errors that are introduced by the measurement equipment is a necessary prerequisite for reproducible measurements and reliable results. However, technical artefacts often remain unpublished. Here we report on a sudden change of luminescence intensity observed while measuring IR-RF signals from K-feldspar extracts. The measurements were carried out on a lexsyg research reader. A lateral movement of the sample carrier up to 0.5mm relative to the photomultiplier tube and the irradiation source, causes a change in the sample geometry. This movement results in inter-aliquot scatter during the measurement of IR-RF. Two solutions are discussed to remove this effect: (I) data post-processing and (II) design change by the manufacturer. Our study so far is limited to IR-RF measurements on a single luminescence reader and suggests due caution in the identification of such systematic errors.